PENGGUNAAN ELLIPTICAL EDITING UNTUK MEMBANGUN SURPRISE DALAM EDITING FILM “BAJING LONCAT” - Tegar Dyon Muhammad; Arif Sulistiyono; Andri Nur Patrio (Institut Seni Indonesia Yogyakarta, 2020)
ABSTRACT In writing a scenario, there are elements that can support development of the story, one of it is